Lexical semantic study of legal terms in English and Uzbek languages (Journal of Pedagogical Inventions and Practices, 2022)
The term comes from the Latin "terminus" - has meanings such as check, limit, border mark, and is a word or combination of words that clearly expresses the concept of something related to science, technology, and other fields, and the scope of use is limited to these fields. A. Reformatsky defines the term as follows.